2016
DOI: 10.1158/1078-0432.ccr-15-2346
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Epigenetic Signature for Early Diagnosis in Lung Cancer

Abstract: Purpose: Lung cancer remains as the leading cause of cancer-related death worldwide, mainly due to late diagnosis. Cytology is the gold-standard method for lung cancer diagnosis in minimally invasive respiratory samples, despite its low sensitivity. We aimed to identify epigenetic biomarkers with clinical utility for cancer diagnosis in minimally/noninvasive specimens to improve accuracy of current technologies. Experimental Design: The identification of novel epigenetic biomarkers in stage I lu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 46 publications
6
85
0
1
Order By: Relevance
“…The frequent inactivation of TRIM58 via hypermethylation observed even in early-stage cases from our panel of primary LADC cases was consistent with the findings of a very recent report [11] in which Diaz-Lagares et al . identified TRIM58 as one of four genes that consistently exhibited CGI hypermethylation in non-small cell lung cancers (NSCLCs) relative to non-malignant lung tissues.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The frequent inactivation of TRIM58 via hypermethylation observed even in early-stage cases from our panel of primary LADC cases was consistent with the findings of a very recent report [11] in which Diaz-Lagares et al . identified TRIM58 as one of four genes that consistently exhibited CGI hypermethylation in non-small cell lung cancers (NSCLCs) relative to non-malignant lung tissues.…”
Section: Discussionsupporting
confidence: 93%
“…identified TRIM58 as one of four genes that consistently exhibited CGI hypermethylation in non-small cell lung cancers (NSCLCs) relative to non-malignant lung tissues. In addition, Diaz-Lagares and colleagues found that this hypermethylation was associated with transcriptional silencing in early-stage (stage I) NSCLCs, regardless of smoking status, and identified a DNA methylation signature model based on those four genes that yielded high diagnostic accuracy for NSCLCs even in minimally invasive samples, such as bronchial fluids [11]. According to reference databases in which gene expression profiles of normal tissue have been generated using next-generation RNA sequencing technologies, such as RNA-seq Atlas (http://medicalgenomics.org/rna_seq_atlas) and RefEx (http://refex.dbcls.jp/), TRIM58 mRNA was not detected in most normal tissues although higher expression of this gene is observed in the lung relative to the levels in various other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4B shows the 20 TSGs with largest differences in methylation between tumour and normal samples. The literature supports the detected methylation differences: Differential promoter methylation for cysteine dioxygenase 1 (CDO1, mean QSEA methylation level of 4% in normal and 78% in PDX) has already been described as part of a DNA methylation signature to detect minimally and non-invasive lung cancer (3234). Other prominent methylation markers of NSCLC are, for example, paired box 6 (PAX6, mean QSEA methylation level of 7% in normal and 79% in PDX) whose promoter hypermethylation has been found to be significantly associated with poor overall survival (35) but also genes like CDX2, CEBPA, HOXB13 and SOX11, that are well described epigenetically regulated genes involved in tumourigenesis of several cancers (3640).…”
Section: Resultsmentioning
confidence: 65%
“…A large number of studies have reported that genes with aberrant promoter methylation are significantly correlated with lung cancer 1013. Located on the human chromosome 9p21, the INK4/ARF locus encodes three cell-cycle inhibitory proteins involving p15 INK4B , p14 ARF , and p16 INK4A ; p16 INK4A is encoded by cyclin-dependent kinase inhibitor 2A ( CDKN2A ), p14 ARF is encoded by an alternative reading frame of CDKN2A, and p15 INK4B is encoded by cyclin-dependent kinase inhibitor 2B ( CDKN2B ), which plays roles in the regulation of p53 and retinoblastoma pathways 1416.…”
Section: Introductionmentioning
confidence: 99%